2003
DOI: 10.1353/dem.2003.0023
|View full text |Cite
|
Sign up to set email alerts
|

Welfare work requirements and child well-being: Evidence from the effects on breast-feeding

Abstract: Reardon, two anonymous referees, and the editor for helpful comments. The opinions and conclusions expressed herein are solely those of the authors and should not be construed as representing the opinions or policy of any of the sponsors or related agencies. ABSTRACTA central theme of welfare reform is recipients are required to engage in work activities. In many states these work requirements apply to mothers whose children are a few months old, potentially increasing the costs and decreasing the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 30 publications
3
38
0
2
Order By: Relevance
“…These laws generally are grouped into 7 major areas: public breastfeeding; exemption from jury duty for new mothers; workplace accommodations; health, education and insurance measures; custody/visitation; and miscellaneous provisions (Vance 2005). However, I found that variations in breastfeeding laws were extremely weak instruments, consistent with previous research (Haider et al 2003). Therefore, I use only formula prices to identify the breastfeeding equation.…”
Section: Data and Sample Considerationssupporting
confidence: 80%
“…These laws generally are grouped into 7 major areas: public breastfeeding; exemption from jury duty for new mothers; workplace accommodations; health, education and insurance measures; custody/visitation; and miscellaneous provisions (Vance 2005). However, I found that variations in breastfeeding laws were extremely weak instruments, consistent with previous research (Haider et al 2003). Therefore, I use only formula prices to identify the breastfeeding equation.…”
Section: Data and Sample Considerationssupporting
confidence: 80%
“…But it is clear that increased pressure on mothers to enter paid employment without flexibility can have negative consequences. For instance, a statistical analysis of the impact of welfare reforms implemented in the United States in 1996 shows a small but significant negative effect on average levels of breastfeeding among low-income mothers (Haider et al, 2003).…”
Section: The Production Of Care Servicesmentioning
confidence: 99%
“…Researchers have suggested an unintended consequence of this act may have reduced the breastfeeding capacity for low-income mothers, including African-American mothers. One analysis concluded that if the welfare reform act had not been implemented, breastfeeding rates 6 months after birth would have been 5.5% higher (Haider, Jacknowitz, & Schoeni, 2003).…”
Section: Discussionmentioning
confidence: 99%